THE LEGAL ENFORCEMENT OF CONSUMER PROTECTION LAW IN THE CIRCULATION OF IMPORTED PHARMACEUTICALS: A Comparative Study Between Indonesia and Malaysia - Anis Abdul Rauf; Chairul Fahmi; Muhammad Husnul (JURISTA: Jurnal Hukum dan Keadilan, 2026)
The circulation of imported pharmaceutical products in the era of globalization presents significant challenges to consumer protection, particularly regarding safety, quality, and halal assurance. Indonesia and Malaysia, as countries with predominantly Muslim populations, have a strategic interest in ensuring that imported medicines circulating in domestic markets comply with health standards and consumer protection principles. This study aims to analyse and compare the enforcement of consumer protection laws in the circulation of imported medicines in both countries, covering regulatory frameworks, supervisory institutions, registration mechanisms, and sanctions for violations. The research employs normative legal methods, including the statutory, comparative, and conceptual approaches. The study is expected to provide an in-depth understanding of the legal framework and oversight mechanisms for imported medicines and serve as a reference for strengthening consumer protection policies in the pharmaceutical sector.